The Influence of Company Size, Leverage, Institutional Ownership and Board of Commissioners Size on Corporate Social Responsibility Disclosure - Mawidya Laifa; Jessy Sitorus; Sefryanto Berto Berto; Meilisa Meilisa (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2022)
This study aims to examine the impact of firm size, leverage, institutional ownership and the size of the board of commissioners on the disclosure of corporate social responsibility, both partially and simultaneously. The issue of Corporate Social Responsibility disclosure is related to the description of the relationship between the corporation and various stakeholders, as well as the environment. The company's relationship with the community is not only measured by how much people use the products and services produced by the company, but what is more important is how much the company provides benefits to the community and the surrounding environment. The population in this study has all manufacturing companies listed on the Indonesia Stock Exchange for the 2016 - 2020 period as many as 177 companies and their samples with a total of 360 units of analysis. The research method applies multiple linear regression analysis techniques. The result of this research is that the variable of company size and institutional ownership partially has no impact on the disclosure of corporate social responsibility. The variable of leverage and the size of the board of commissioners partially have an impact on the disclosure of corporate social responsibility. The variables of the influence of firm size, leverage, institutional ownership and the size of the board of commissioners simultaneously have an impact on the disclosure of corporate social responsibility